2020
DOI: 10.1088/1674-1056/ab5fc5
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamics simulation of atomic hydrogen diffusion in strained amorphous silica*

Abstract: Understanding hydrogen diffusion in amorphous SiO2 (a-SiO2), especially under strain, is of prominent importance for improving the reliability of semiconducting devices, such as metal–oxide–semiconductor field effect transistors. In this work, the diffusion of hydrogen atom in a-SiO2 under strain is simulated by using molecular dynamics (MD) with the ReaxFF force field. A defect-free a-SiO2 atomic model, of which the local structure parameters accord well with the experimental results, is established. Strain i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…[1,2] The diffusion of hydrogen atoms on metal surfaces is an important step in many catalytic reactions, such as the formation of ammonia in the Haber-Bosch process, [3] the synthesis of hydrocarbons, [4] and the generation and oxidation of H 2 in electrochemistry. [5,6] Numerous experimental [7][8][9][10][11][12] and theoretical [13][14][15][16][17][18][19] studies have been carried out to understand the process of hydrogen diffusion on solid surfaces. Experimental techniques such as helium atom scattering (HAS), [9] scanning tunneling microscopy (STM), [10,11] inelastic electron tunneling spectroscopy (IETS), [10,11] high-resolution electron energy loss spectroscopy (HREELS), [20] and linear optical diffraction (LOD) techniques [7] have been used to study the quantum effects of hydrogen atoms during diffusion.…”
Section: Introductionmentioning
confidence: 99%
“…[1,2] The diffusion of hydrogen atoms on metal surfaces is an important step in many catalytic reactions, such as the formation of ammonia in the Haber-Bosch process, [3] the synthesis of hydrocarbons, [4] and the generation and oxidation of H 2 in electrochemistry. [5,6] Numerous experimental [7][8][9][10][11][12] and theoretical [13][14][15][16][17][18][19] studies have been carried out to understand the process of hydrogen diffusion on solid surfaces. Experimental techniques such as helium atom scattering (HAS), [9] scanning tunneling microscopy (STM), [10,11] inelastic electron tunneling spectroscopy (IETS), [10,11] high-resolution electron energy loss spectroscopy (HREELS), [20] and linear optical diffraction (LOD) techniques [7] have been used to study the quantum effects of hydrogen atoms during diffusion.…”
Section: Introductionmentioning
confidence: 99%
“…The previous research has shown that the fracture behavior of the silica glass is influenced by various external factors, such as model size, quenching rate, temperature, and strain rate. [17][18][19][20][21][22][23][24][25] The tensile strength will increase rapidly to a plateau level when the strain rate exceeds 2.5 × 10 11 s −1 and no more localization of damage in the sample. Importantly, the transition from brittleness to ductility was also observed with quenching rate and strain rate.…”
Section: Introductionmentioning
confidence: 99%
“…Water diffusion in silica is a crucial process in predicting and controlling the mechanical response of silicate materials. The presence of water is known to affect the physical and chemical properties of silicates significantly; however, its atomistic mechanism has been argued for many decades. Stress corrosion cracking (SCC) is an archetypal example where subcritical crack growth is observed under a moist environment. With moisture, a crack tip of silica glass is found filled with water.…”
mentioning
confidence: 99%